Paddy farmers and success in knowledge transfer / Dang Merduwati Hashim - Hashim, Dang Merduwati (2006)
This study is an exploratory study and aims to generate a theory of success in knowledge transfer within a substantive setting. Based on the nature of the study, a qualitative approach using Glaser and Strauss (1967) grounded theory methodology is chosen. Eight farmers participated in the research. Data collection started by interviewing one farmer who is currently the Secretary for 10 Tonnes Paddy Club. Theoretical sampling is used in this study. All interviews are recorded, transcribed, analyzed, conceptualized, coded and categorized. The analytical process began with the writing of memos that described the scenes, events and behaviors of participants. The first theoretical memo was written on 31st. Jan 2005 prior to the first interview. As codes and memos build up, the relationships theoretical coding emerged. Observations were also carried out during the one-to one interview, the focus group interview and when the DOA officers met the farmers for short briefings. The research process, depicting the journey in generating the grounded theory and content of the emerging theory has been presented in the form of theoretical memos.